Pengaruh Pemanfaatan Media Audio Visual Berbasis Web terhadap Motivasi dan Hasil Belajar Pendidikan Agama Islam pada Siswa di SMA Muhammadiyah 02 Medan - Harahap, Weni Aulia (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The research aims to analyze the influence of utilizing web-based audio-visual media on students’ motivation and learning outcomes in Islamic Religious Education at SMA Muhammadiyah 02 Medan. The research method employed was quantitative with a quasi-experimental design, specifically the one-group pre-test post-test design. The population consisted of all tenth-grade students, with a sample of 60 students. The instruments used were a learning motivation questionnaire and pre-test and post-test scores of learning outcomes. The data were analyzed using linear regression and product-moment correlation to measure the relationship between web-based audio-visual media and students’ learning motivation, as well as a paired sample t-test to examine differences in learning outcomes before and after the treatment. The results indicate that the use of web-based audio-visual media has a significant effect on enhancing learning motivation, as evidenced by the regression analysis with a significance value of 0.00 < 0.05. Furthermore, the product-moment correlation test shows a calculated r-value of 0.469. In addition, the use of web-based audio-visual media significantly affects students’ learning outcomes, as shown by the t-test result with a t-value of -17.626, degrees of freedom (df = 59), and a significance level (Sig. 2-tailed) of 0.000 < 0.05. In conclusion, the utilization of web-based audio-visual media provides a significant positive effect on students’ motivation and learning outcomes in Islamic Religious Education at SMA Muhammadiyah 02 Medan.